KINERJA MESIN BUBUT GEMINIS DITINJAU DARI KEBULATAN BENDA KERJA - Eko Yudo; Ariyanto Ariyanto (JURNAL INTEGRASI, 2019)
Machine tools in manufacturing that produce workpieces with high accuracy are needed for the world of Manufacturing Industry. Machine tools that produce workpieces (low roundness deviation) with good quality will produce prices comparable to those offered. So that requires more optimum maintenance and maintenance of the engine. Mechanical Laboratory Manufacturing Polytechnic of Bangka Belitung State has several lathes to produce workpieces in the form of student training products, machined parts and production activities with a precision size, this lathe has been used for approximately 20 years, the usage of which has been long can lead to changes in machine geometry deviations. Deviations that occur will affect the quality of the product produced. Among the lathes there are 3 units of Geminis lathes. To find out the roundness deviation that occurs after being used in the teaching and learning process and the manufacture of spare parts for 20 years and to determine the feasibility of a lathe if it is used to process workpieces with a certain size tolerance, it is necessary to do testing. The test that is done is testing the geometric of the machine on the roundness of the workpiece .. The results of the cutting process of the test object will be measured by rounding the analysis by means of a minimum circle area. The three geminis have an average deviation of 45.33 μm and the smallest average deviation of 20 μm can produce workpieces with tolerances above 41 μm.